Medicare reimbursement trends from 2000 to 2020 in head and neck surgical oncology. Issue 7 (13th April 2022) - Quereshy, Humzah A.; Quinton, Brooke A.; Cabrera, Claudia I.; Li, Shawn; Tamaki, Akina; Fowler, Nicole
Abstract: Background: Considering limited data exploring reimbursement trends at the subspecialty level within head and neck surgical oncology, we sought to characterize these trends for head and neck‐specific codes from 2000 to 2020. Methods: Using the Centers for Medicare and Medicaid Services' Physician Fee Schedule Look‐Up Tool, reimbursement data, adjusted to 2020 U.S. dollars, for 37 head and neck surgical oncologic procedure codes were collected from 2000 to 2020. Results: From 2000 to 2020, despite gross reimbursement for all head and neck procedures increasing by 23.2%, when adjusted for inflation, physician reimbursement decreased by 19.4%. Only 4 of 37 examined codes increased in net reimbursement over the study period. Conclusion: Medicare reimbursement for the most common head and neck oncologic procedure codes decreased from 2000 to 2020. Further research is necessary to explore the implications of these trends on the delivery of patient care.